Knowledge generated in low-and middle-income countries can shape the future of acute leukemia therapies worldwide: the case of Clínica Ruiz in Puebla, Mexico - Alberto-López, Lidia Joanna; Gómez-Cabrera, Miguel Ángel; Chávez-Martinez, Sofia; Anaya-Valdés, Paola Andrea; Robles-Nasta, Max; Olivares-Gazca, Juan Carlos; Ruiz-Delgado, Guillermo J.; Ruiz-Argüelles, Guillermo J. (Frontiers in Hematology, 2025)
Acute leukemias remain a major health challenge worldwide, particularly in children, adolescents, and older adults, with marked disparities in outcomes between high- and low-income regions. For more than four decades, The Clínica Ruiz in Puebla, Mexico, has contributed to leukemia research and treatment through pioneering strategies adapted to resource-constrained environments. The early adoption of immunophenotyping improved diagnostic accuracy in Mexico, while studies on nutritional status at diagnosis underscored its prognostic impact in pediatric acute lymphoblastic leukemia (ALL). The institution also demonstrated the feasibility and efficacy of pediatric-inspired regimens in adolescents and young adults with ALL, challenging the use of more toxic adult protocols. In acute myeloid leukemia (AML), contributions have included the description of regional prevalence patterns, molecular characterization, and the development of innovative outpatient therapeutic approaches. Clínica Ruiz further established one of the most active hematopoietic stem cell transplantation (HSCT) programs in Latin America, introducing cost-effective outpatient transplantation models—known as the “Mexican method”—for both autologous and allogeneic modalities, including haploidentical transplants. Collectively, these advances illustrate how strategies designed in Mexico for limited-resource settings have not only improved leukemia care locally but have also informed practices globally.